Empowering Innovation: The Role of Digital Leadership in Shaping Gen Z and Gen Y Performance with Creativity as a Moderator - Rahmandika, Harris Prasetya; Santoso, Yusuf Akbar; Imani, Dilla; Herachwati, Nuri (Universitas Airlangga, 2025)
Objective: This study develops a quantitative model that integrates digital leadership, innovative work behavior, and employee performance, while also examining the moderating effect of creativity from the perspective of Upper Echelons Theory. Design/Methods/Approach: This study employs PLS-SEM to examine the relationships among variables, using data collected from full-time Gen Z and Gen Y employees across various industries. Findings: The study shows that digital leadership positively and significantly influences innovative work behavior, which also exerts a positive and significant effect on employee performance. In addition, digital leadership directly enhances employee performance. The results further indicate that innovative work behavior partially mediates the effect of digital leadership on employee performance. Finally, the moderating analysis suggests that high levels of employee creativity weaken the relationship between digital leadership and employee performance. Originality/Value: This study contributes to existing literature on the field of leadership in the perspective of Upper Echelons Theory, especially that focus on the field of digital leadership. Practical/Policy implication: Theoretical aspects of the study advance our understanding of digital leadership and its mechanisms. For practice, the results provide actionable guidance for top management, particularly in organizations that employ Gen Z and Gen Y workers.